Embracing the Future of Hotel Hospitality Digital Marketing - Tamzil Yusuf; Yulianti Keke (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
Hospitality has been part of our life especially for travel on tourism, since early days of civilization to the current digital age civilization. Hotel Hospitality Digital Marketing gave birth to a lot of aspects from tech to marketing development, from AI tech advancement to Sustainable Marketing. Yet, it’s not enough to embrace the future due to facing pandemic. Therefore, a different method developed during post-pandemic regulation is S-D logic with the aid of customer commitment. While it is good to find a different method, we should also recognize the current struggle of exploitative system in order to embrace the future. There, we could handle human, nature, and AI properly and work towards the future of Hotel Hospitality Digital Marketing.